2015
DOI: 10.1111/rda.12479
|View full text |Cite
|
Sign up to set email alerts
|

B‐Mode and Doppler Sonography of the Mammary Glands in Dairy Goats for Mastitis Diagnosis

Abstract: This study aimed to evaluate the sonographic characteristics of the udder and teats and to determine the Doppler indexes of mammary artery in healthy and undergoing subclinical and clinical mastitis goats. Thirty animals among Saanen and Alpine Brown goats were arranged in three groups, healthy goats (HG), goats with subclinical mastitis (SMG) and goats with clinical mastitis (CMG). Using the B-mode, the sonographic characteristics (echotexture and echogenicity) and biometry (diameter and area of the udder cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 6 publications
0
18
1
Order By: Relevance
“…The application of ultrasound technology for the determination of milk compositions would offer several benefits that are not currently available with the use of on-farm equipment or standard laboratory testing. Ultrasound examination is a non-invasive, non-destructive method placing minimal stress on the animal [8]. Ultrasound imaging is easily accessible and portable ultrasound units can be used in developing countries or in rural areas that have limited access to laboratory services or are not willing to pay for shipping of multiple milk samples.…”
Section: Introductionmentioning
confidence: 99%
“…The application of ultrasound technology for the determination of milk compositions would offer several benefits that are not currently available with the use of on-farm equipment or standard laboratory testing. Ultrasound examination is a non-invasive, non-destructive method placing minimal stress on the animal [8]. Ultrasound imaging is easily accessible and portable ultrasound units can be used in developing countries or in rural areas that have limited access to laboratory services or are not willing to pay for shipping of multiple milk samples.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound images of the mammary gland in ruminant species have been described as exhibiting granular texture due to the presence of less echoic lobular alveoli being dispersed within hyperechoic connective tissue (Olechnowicz and Jaśkowski, 2009;Santos et al, 2015;Barbagianni et al, 2017). The mammary parenchyma in healthy dairy goats appears as a hyperechoic structure with slightly coarse echotexture (Fasulkov, 2012;Santos et al, 2015;Barbagianni et al, 2017). Occasionally, anechoic lactiferous ducts or larger blood vessels are identified during the scanning of the udder (Ruberte et al, 1994;Nudda et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Same study determined that the increase in SPV was related to increased blood flow to affected region due to increased inflammation, while the decrease in RI was suggested to be related to an increase in vascular resistance due to the same increased blood flow (18). Braun and Hoegger (5) reported a mean maximum blood flow velocity of 45.4 cm/sec, mean velocity of 33.5 cm/sec, and minimum velocity of 25.8 cm/sec before sedation in 29 healthy Swiss Brown cows, which were sedated.…”
Section: Discussionmentioning
confidence: 96%
“…Berger et al reported that pulsed wave Doppler ultrasonography can be used to analyze blood flow to udder, sharing the finding that ultrasonographic parameters regarding blood flow to udder increased with milk yield (1). Pulsed wave Doppler ultrasonography is used to measur values such as Time-Averaged Maximum Velocity (TAMV), blood flow volume, Systolic Peak Velocity (SPV) and Resistant Index (RI) in vessels supplying blood to udders (10,17,18,19).…”
Section: Introductionmentioning
confidence: 99%